A process-output classification for customer participation in services. Issue 5 (19th October 2015) - Dong, Beibei; Sivakumar, K.
Abstract : Purpose: – The purpose of this paper is to propose a classification for customer participation (CP) in services. Furthermore, it develops research propositions examining the moderating role of the proposed classification on the link between the magnitude of CP and service outcomes. Design/methodology/approach: – Building on the process-output framework, the paper explores the contingent nature of the effect of CP magnitude on service outcomes (satisfaction and efficiency). Findings: – The research propositions suggest that specific output enhances the positive effect of CP magnitude on satisfaction but also intensifies the negative effect of CP magnitude on efficiency; conversely, generic output diminishes the positive effect of CP magnitude on satisfaction but mitigates the negative effect of CP magnitude on efficiency. The effect of CP magnitude on satisfaction is stronger for a structured participation process than for an unstructured process; while the negative effect of CP magnitude on efficiency is stronger for an unstructured participation process than for a structured process. Further, process structure has an asymmetric enhancing effect on the negative link between CP magnitude and efficiency such that the enhancing effect of process structure is stronger for specific output than for generic output; likewise, process structure has an asymmetric enhancing effect on the positive link between CP magnitude and satisfaction such that the enhancing effect of structure is stronger for generic output than for specific output. Research limitations/implications: – The research provides a conceptual approach to classify CP. Further research can focus on empirical validation as well as expanding the scope and variables examined. Practical implications: – The research points to guidelines to structure CP activities based on the nature of the participation process and the type of service output to achieve the competing goals of customer satisfaction and efficiency. Originality/value: – The proposed classification offers a new method to visualize CP in services. The framework is applicable to a wide variety of services, service contexts, and resources contributed by customers during their participation.